MODELING OF SALINITY PARAMETERS USING MIKE-21 SOFTWARE IN PANGANDARAN WATERS - Roberto Patar Pasaribu; Anasri Tanjung; Rifal Ramadhany; Rini Handayani (Aurelia Journal, 2023)
Salinity is the level of saltiness or salt content dissolved in water. Salinity is the total concentration of dissolved ions in water. The amount of salinity greatly affects the growth and survival rate of biota in the waters. To find out the salinity can be done by direct measurements in the field or by modeling. The purpose of this study was to determine the value of the salinity parameter by modeling salinity using the MIKE-21 Software at the mouth of the Citanduy River, Pangandaran Waters. MIKE-21 software is a hydrodynamic modeling software used to predict marine physics parameters, one of which is the value of the salinity parameter. The results of salinity modeling carried out at 4 observation stations at the mouth of the Citanduy River obtained an average value of salinity at high tide at the mouth of the river was 17.05 ppt and at low tide was 14.31 ppt.